1995
DOI: 10.1105/tpc.7.11.1941
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of maize histone deacetylases by HC toxin, the host-selective toxin of Cochliobolus carbonum.

Abstract: HC toxin, the host-selective toxin of the maize pathogen Cochliobolus carbonum, inhibited maize histone deacetylase (HD) at 2 pM. Chlamydocin, a related cyclic tetrapeptide, also inhibited HD activity. The toxins did not affect histone acetyltransferases. After partia1 purification of histone deacetylases HD1-A, HD1-B, and HD2 from germinating maize embryos, we demonstrated that the different enzymes were similarly inhibited by the toxins. lnhibitory activities were reversibly eliminated by treating toxins wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(69 citation statements)
references
References 58 publications
1
68
0
Order By: Relevance
“…HC toxin is a cyclic tetrapeptide originally identified as a host-selective toxin from the maize pathogenic fungus Cochliobolus (Helminthosporium) carbonum (Mottamal et al 2015), and it was shown to inhibit class I HDAC enzymes (HDAC1, -2, -3 and -8) in mammalian cells (Brosch et al 1995, Hildmann et al 2006. Herein, we report that HC toxin activates two exercise-activated pathways in C2C12 myotubes: AMPK and Akt pathways.…”
Section: Introductionmentioning
confidence: 99%
“…HC toxin is a cyclic tetrapeptide originally identified as a host-selective toxin from the maize pathogenic fungus Cochliobolus (Helminthosporium) carbonum (Mottamal et al 2015), and it was shown to inhibit class I HDAC enzymes (HDAC1, -2, -3 and -8) in mammalian cells (Brosch et al 1995, Hildmann et al 2006. Herein, we report that HC toxin activates two exercise-activated pathways in C2C12 myotubes: AMPK and Akt pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Other SCCEs such as trichostatin A (TSA), an antifungal compound produced by Streptomyces species [21,22] and HC-toxin, produced by Cochliobolus carbonum during maize leave infection, inhibits class I and class II HDAC activity [23]. Already in 1978 it was demonstrated that butyrate, a short chain fatty acid produced by anaerobic bacterial fermentation, induces differentiation of erythroleukemic cells via inhibition of HDACs [24].…”
Section: Introductionmentioning
confidence: 99%
“…[88] In AS1387392, the MePro residue of FR235222 is replaced by proline. [90] It can significantly inhibit HDAC activity in Physarum spp., maize, and chicken erythrocytes at a concentration of 2 mg mL À1 . AS1387392 also shows potent inhibitory activity against splenocyte proliferation (IC 50 = 4.6 nm), similar to that of FR235222 (IC 50 = 5.0 nm).…”
Section: Fr235222mentioning
confidence: 99%